EFFECT OF TEMPERATURE ON THE NITRIFICATION AND MINERALISATION OF SOIL - Amin, Mohammad; Flowers, T.H. (Journal of Research (Science), 2004)
A laboratory incubation experiment at 20, 15, 10, 5 and 0oC was carried out on nitrification and mineralisation in fresh soils samples at Glasgow University, Glasgow, United Kingdom during 1995. Both nitrification and mineralisation rates decreased with decreasing temperature in all soils. The nitrification and mineralisation rates vary in different soils due to difference in soil properties and presence of variation  in population of nitrifying bacteria. The measured nitrification rates at 0 oC indicated that nitrifying bacteria can survive and nitrify applied ammonium sulphate at the lowest temperature tested. The natural logarithm of nitrification and mineralisation rates against reciprocal of absolute temperature showed a good fit to a straight line Arrhenius relationship for all soil. The temperature of 5 to 15 oC was suitable for nitrifying and mineralizing bacteria for incubational studies of nitrification and mineralisation. The Arrhenius relationship was improved on data of 5 to 15 K. The Arrhenius relationship for ammonium disappearance and nitrate formation were similar in all soils while mineralisation significantly varied for each soil.